Impact of Iron Supplementation on Children with Severe Attention Deficit Hyperactive Disorder- A Randomized Clinical Trial - Saha, Dipa; Parvin , Jobaida; Khan, Husne Ara; Mistry, Banita; Begum, Shameem Ara; Hoque, Seikh Azimul; Sarker , Shyamal; Saha, Narayan Chandra (Bangladesh Journal of Child Health, 2024)
Background: Iron acts as a risk factor and psychostimulant modulator in treatment of ADHD with iron deficiency anemia. Objective: To see the impact of iron supplementation on severe ADHD children. Materials and Methods: This randomized controlled trial conducted in the OPD, Pediatric Neurology from July 2019 to January 2020; NINS 50 children of severe ADHD with iron deficiency were enrolled. Participants were randomized into group A (25 cases) given a combination of Methylphenidate and iron, and group B (25 cases) given Methylphenidate alone for 3 months. Conner’s rating scale, CBC and serum ferritin was evaluated after one and three months, severity was compared between treatment groups. Analysis of data was done by SPSS version of 22.0. Result: Combined ADHD, poor academic performance, poor appetite, frequent infection was common features of IDA among the cases. All hematological parameters were increased from baseline to 1 month and 3 months follow up in all cases but significantly improved in Iron receiving groups. the severity of T scores of ADHD index were decreased at 1 month (p=0.047) and 3 months (p= 0.026) after intervention. Conclusion: This study concluded that iron supplementation along with psychostimulant found better response in severe ADHD children BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 48-53